Isotope effects on intrinsic rotation in hydrogen, deuterium and tritium plasmas. (9th March 2023) - Nave, M.F.F.; Delabie, E.; Ferreira, J.; Garcia, J.; King, D.; Lennholm, M.; Lomanowski, B.; Parra, F.; Fernandez, P.R.; Bernardo, J.; Baruzzo, M.; Barnes, M.; et al.
Abstract: The isotope effect on intrinsic rotation was studied at the Joint European Torus (JET) tokamak. With the unique capability of JET to operate with tritium (T), for the first time, experiments in hydrogen (H), deuterium (D) and T in Ohmic plasmas were compared. Two rotation reversals per isotope type are observed in plasma density scans spanning the linear and the saturated Ohmic confinement regimes. A clear isotope mass dependence is observed at the higher densities. The magnitude of the core rotation was found to depend on isotope mass, with stronger co-current rotation observed in H. Change on intrinsic rotation characteristics coexist with a stronger thermal energy confinement in T.